PENGARUH PROMOSI PENJUALAN DAN KEMUDAHAN PENGGUNAAN TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA I-SAKU DI MINIMARKET INDOMARET MELONG 07 CIMAHI - Budi Prasetiyo (JURNAL BISNIS dan TEKNOLOGI, 2023)
Abstract: The main purpose of this study was to determine the effect of sales promotion and ease of use on purchasing decisions on i-saku users at the Indomaret Melong 07 Cimahi minimarket. The research method used is descriptive and associative methods. The unit analysis in this study is i-saku users who have registered at the Indomaret Melong 07 Cimahi Minimarket. The data collection technique in this study used a judgment sampling approach. The type of data used is primary data while the instrument used in data collection is a questionnaire. The results showed that there was an effect of Sales Promotion and Ease of Use on Purchase Decisions for i-saku users at Minimarket Indomaret Melong 07 Cimahi, while the effect was 70%. Partially, there is an effect of Sales Promotion (X1) on Purchase Decision (Y), which is 36.8%. For partial effect, Ease of Use (X2) on Purchase Decision (Y) is 33.2%. Keywords: Sales Promotion, Ease of Use, Retail Business, Purchase Decision.